Early Auditory Event-Related Potentials Are Modulated by Alphabetic Literacy Skills in Logographic Chinese Readers - Zhang, Yubin; Pattamadilok, Chotiga; Lau, Dustin Kai-Yan; Bakhtiar, Mehdi; Yim, Long-Ying; Leung, Ka-Yui; Zhang, Caicai (Frontiers in Psychology, 2021)
The acquisition of an alphabetic orthography transforms speech processing in the human brain. Behavioral evidence shows that phonological awareness as assessed by meta-phonological tasks like phoneme judgement, is enhanced by alphabetic literacy acquisition. 　The current study investigates the time-course of the neuro-cognitive operations underlying this enhancement as revealed by event-related potentials (ERPs). Chinese readers with and without proficiency in Jyutping, a Romanization system of Cantonese, were recruited for an auditory onset phoneme judgement task; their behavioral responses and the elicited ERPs were examined. Proficient readers of Jyutping achieved higher response accuracy and exhibited more negative-going ERPs in three early ERP time-windows corresponding to the P1, N1, and P2 components. The phonological mismatch negativity (PMN) component exhibited sensitivity to both onset and rhyme mismatch in the speech stimuli, but it was not modulated by alphabetic literacy skills. The sustained negativity in the P1-N1-P2 time-windows is interpreted as reflecting enhanced phonetic/phonological processing or attentional/awareness modulation associated with alphabetic literacy and phonological awareness skills.